A83-01 and DMH1 effects in the zebrafish spermatogonial niche: Unraveling the roles of TGF-β and BMP signaling in the Fsh-mediated spermatogonial fate - Fernandes da Costa, Daniel [UNESP] (2024)
Transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP) signaling has fundamental roles in the regulation of the stem cell niche for both embryonic and adult stem cells. In zebrafish, male germ stem cell niche is regulated by follicle-stimulating hormone (Fsh) through different members of the TGF-β superfamily. On the other hand, the specific roles of TGF-β and BMP signaling pathways are unknown in the zebrafish male germ stem cell niche. Considering this lack of information, the present study aimed to investigate the pharmacological inhibition of TGF-β (A83-01) and BMP (DMH1) signaling pathways in the presence of recombinant zebrafish Fsh using testicular explants. We also reanalyzed single cell-RNA sequencing (sc-RNA-seq) dataset from adult zebrafish testes to identify the testicular cellular sites of smad expression, and to understand the physiological significance of the changes in smad transcript levels after inhibition of TGF-β or BMP pathways. Our results showed that A83-01 potentiated the pro-stimulatory effects of Fsh on spermatogonial differentiation leading to an increase in the proportion area occupied by differentiated spermatogonia with concomitant reduction of type A undifferentiated (Aund) spermatogonia. In agreement, expression analysis showed lower mRNA levels for the pluripotency gene pou5f3, and increased expression of dazl (marker of type B spermatogonia and spermatocyte) and igf3 (pro-stimulatory growth factor) following the co-treatment with TGF-β inhibitor and Fsh. Contrariwise, the inhibition of BMP signaling nullified the pro-stimulatory effects of Fsh, resulting in a reduction of differentiated spermatogonia and increased proportion area occupied by type Aund spermatogonia. Supporting this evidence, BMP signaling inhibition increased the mRNA levels of pluripotency genes nanog and pou5f3, and decreased dazl levels when compared to control. The sc-RNA-seq data unveiled a distinctive pattern of smad expression among testicular cells, primarily observed in spermatogonia (smad 2, 3a, 3b, 8), spermatocytes (smad 2, 3a, 8), Sertoli cells (smad 1, 3a, 3b), and Leydig cells (smad 1, 2). This finding supports the notion that inhibition of TGF-β and BMP signaling pathways may predominantly impact cellular components within the spermatogonial niche, namely spermatogonia, Sertoli, and Leydig cells. In conclusion, our study demonstrated that TGF-β and BMP signaling pathways exert antagonistic roles in the zebrafish germ stem cell niche. The members of the TGF-β subfamily are mainly involved in maintaining the undifferentiated state of spermatogonia, while the BMP subfamily promotes spermatogonial differentiation. Therefore, in the complex regulation of the germ stem cell niche by Fsh, members of the BMP subfamily (pro-differentiation) should be more predominant in the niche than those belonging to the TGF-β (anti-differentiation). Overall, these findings are not only relevant for understanding the regulation of germ stem cell niche but may also be useful for expanding in vitro the number of undifferentiated spermatogonia more efficiently than using recombinant hormones or growth factors.